Boxes for Katje - Fleming, Candace; Dressen-McQueen, Stacey (New York : Farrar, Straus and Giroux, 2003)
After a young Dutch girl writes to her new American friend in thanks for the care package sent after World War II, she begins to receive increasingly larger boxes.
"Melanie Kroupa Books."
Lexile
Ages 3-8.
Young hoosier book award nominee 2006-2007.
1 7 8 12 13 15 17 18 20 21 25 29 33 34 36
Keywords: Generosity -- Juvenile fiction; World War, 1939-1945 -- Civilian relief -- Juvenile fiction; World War, 1939-1945 -- Civilian relief -- Fiction; Young Hoosier Book Award Nominee 2006-2007.; Netherlands -- Fiction